Photoluminescence properties of AlN homoepilayers with different orientations - Sedhain, A.; Nepal, N.; Nakarmi, M. L.; Al tahtamouni, T. M.; Lin, J. Y.; Jiang, H. X.; Gu, Z.; Edgar, James H. (My University, 2008)
AlN homoepilayers and heteroepilayers were grown on polar c-plane and nonpolar a-plane and m-plane orientations of AlN bulk and sapphire substrates by metal organic chemical vapor deposition. A systematic comparative study of photoluminescence properties of these samples revealed that all AlN homoepilayers c, a and m planes were strain free with an identical band gap of about 6.099 (6.035) eV at 10 (300) K, which is about 42 meV below the band gap of c-plane AlN heteroepilayers grown on sapphire. Also, nonpolar a-plane homoepilayers have the highest emission intensity over all other types of epilayers. We believe that a-plane AlN homoepilayers have the potential to provide orders of magnitude improvement in the performance of new generation deep UV photonic devices.
Keywords: Nitride films; Sapphire; Quantum wells